2000
DOI: 10.1128/iai.68.1.352-359.2000
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of CD8+T Cells In Vivo Impairs Host Defense of Mice Resistant and Susceptible to Pulmonary Paracoccidioidomycosis

Abstract: Using a pulmonary model of infection, we demonstrated previously that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 36 publications
2
44
0
9
Order By: Relevance
“…The reported finding of an increased number of CD8z in PCM BAL supports the notion that MIP-1a is important in attracting and stimulating this subpopulation. A protective role for CD8z T-cells has been suggested in experimental PCM since its depletion induces a more severe and/or disseminated disease in both resistant and susceptible mice [26]. Cytotoxic CD8z T-cells represent a major defence against intracellular pathogens by the production of IFN-c and cytolytic activity, and may be involved in the clearance of P. brasiliensis cells.…”
Section: Discussionmentioning
confidence: 99%
“…The reported finding of an increased number of CD8z in PCM BAL supports the notion that MIP-1a is important in attracting and stimulating this subpopulation. A protective role for CD8z T-cells has been suggested in experimental PCM since its depletion induces a more severe and/or disseminated disease in both resistant and susceptible mice [26]. Cytotoxic CD8z T-cells represent a major defence against intracellular pathogens by the production of IFN-c and cytolytic activity, and may be involved in the clearance of P. brasiliensis cells.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior is usually associated with efficient killing of intracellular pathogens via production of oxygen or nitrogen radicals [43] and was shown to induce preferential Th1 immunity, a fact that does not occur with susceptible animals [6,13]. In fact, the adaptative immunity of B10.A mice was shown to be mediated by CD8 ϩ T cells and anergy or deletion of the CD4 ϩ T cell subset [6,7,13].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, A/J mice presented a regressive disease with well-organized lesions containing a low number of yeasts, positive cellular immunity, and macrophage activation, resembling the benign forms of PCM [6]. Studies on pulmonary cytokines demonstrated that both mouse strains are able to secrete proinflammatory and anti-inflammatory cytokines, but higher levels of IFN-␥, IL-5, and IL-10 were present in the lungs of susceptible mice [7,8]. Using gene knockout or cytokine-depleted mice, protective immunity to Pb infection was shown to be mediated by IFN-␥, IL-12, and TNF-␣ [9 -12], all macrophage-activating cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the most severe forms of infection are associated with high levels of specific antibodies. 4 Several compounds are used for inhibition of the P. brasiliensis and the neolignan compounds have been used for this purpose. 5 Neolignans are organic dimers derived from oxidative coupling of allyl and propenyl phenols that occur in the Myristicaceae 6-8 and other primitive plant families.…”
Section: Introductionmentioning
confidence: 99%
“…2 Effective treatment regimens are available to control the infectious process and most patients (60-80%) develop fibrotic sequelae that may severely hamper respiratory functions and limit the patient well-being. 2 Antifungal 4 Several compounds are used for inhibition of the P. brasiliensis and the neolignan compounds have been used for this purpose. 5 Neolignans are organic dimers derived from oxidative coupling of allyl and propenyl phenols that occur in the Myristicaceae 6-8 and other primitive plant families.…”
mentioning
confidence: 99%